Features of biology and prospects of modern fishery for pacific herring Clupea pallasii on the shelf of southern Kuril Islands - A. O. Zolotov; A. V. Buslov; S. S. Ponomarev (Известия ТИНРО, 2022)
Biological characteristics and dynamics of stocks and fishery are considered for pacific herring in the South-Kuril fishing district on the data of research surveys and fishery statistics for 2014–2021. Features of the herring wintering and the rates of linear growth and maturation are analyzed. The stock recovery on the shelf of southern Kuril Islands is detected that corresponds to recovery of the whole Sakhalin-Hokkaido population of this species. A sharp increase of the herring abundance in this area is observed nowadays for the first time since the 1940s. According to results of cohort modeling, the commercial biomass of herring in the South-Kuril district has increased from several tens of ton in 2014–2017 to 9,700 t in 2021. The basis of the stock consists of fish aged 3–4 years, 25–29 cm long, that prevailed (76–82 %) in the catches in 2020–2021. The stock increasing is accompanied by expansion of the herring distribution, the aggregations density increasing in spring, complication of the size and age structure, heightening of the average size and age in catches of fixed nets in the spawning season, mass appearance of the juveniles in catches of bottom trawl survey in 2020, and progressive growth of the landing in 2018–2021. The usual place for the herring wintering in this area is the eastern side of the deep-water canyon off the western coast of Kunashir Island. According to updated data, the spawning migrations of herring begin in early-middle April. The producers migrate mainly from the wintering sites to the southern Kunashir Strait, and then along the Pacific side of Kunashir Island to their spawning grounds. The migration along the Okhotsk Sea coast is secondary. The spawning occurs at Kunashir Island in the period from late April to middle May (the timing varies from year to year; the peak of spawning was observed in early May in 2020, but in middle May in 2021). Unlike other populations, the herring of the South-Kuril area do not make extended migrations after the spawning, but feed on adjacent shelf for a long time. Fishery on herring develops rapidly in the South-Kuril fishing district: the annual catch was 140 t in 2018, but reached 1010 t in 2021. Trawl fishery of pacific herring has the highest prospects for coming years. The fishing by Danish seines can be intensified in the waters between Kunashir and Shikotan in the pre-spawning period, though the landing by fixed nets on the spawning grounds can be stabilized if the number of coastal fishing teams will be increased.